ANALYSIS OF FACTORS THAT CONTRIBUTE TO STUDENT ANXIETY WHEN FACING THE FINAL PROJECT IN THE ERA OF EDUCATIONAL DIGITALIZATION - Wijayanti, Keisya Putri; Marsofiyati,; Utari, Eka Dewi (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2025)
This study aims to analyze the contributing factors to student anxiety during the completion of their final project. The anxiety is influenced by a combination of internal factor such as low self-confidence, perfectionist tendencies, lack of motivation, and fear of unsatisfactory outcomes. And the external factors including the role of academic supervisors, time pressure, peer pressure, limited access to data, and institutional demands. This research employs a qualitative descriptive approach through interview and observation involving students from various universities. The finding indicates that anxiety frequently arises during the early stages of the final project, particularly when defining the research title and direction. The effect of anxiety span both psychological and physical aspects, including sleep disturbances, loss of appetite, and emotional instability. Students tend to adopt coping strategies such as time management, relaxing activities, and seeking social support to deal with their anxiety. The study recommends institutional and academic mentor support to facilitate a more effective and less stressful final project experience.